2020
DOI: 10.1108/apjml-02-2020-0081
|View full text |Cite
|
Sign up to set email alerts
|

The importance of knowledge and trust for ethical fashion consumption

Abstract: PurposeThe clothing industry is one of the most polluting industries in the world, although manufacturers and retailers are trying to revert this tendency by applying ethical fashion principles. Drawing on the knowledge–attitude–behavior (KAB) model or practice, this study aims to predict Chinese consumers' purchase intention of ethical fashion by employing and extending the theory of planned behavior (TPB).Design/methodology/approachThe extended TPB model incorporates knowledge of ethical fashion and trust in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 66 publications
(91 reference statements)
3
31
1
2
Order By: Relevance
“…Result demonstrates that product knowledge a positive and significant effect on the consumer purchase intention towards green products, which supports H5. The finding is in favour of the results of previous studies of (Han et al, 2017;Groening et al, 2018;Liu et al, 2021;Zollo et al, 2021). The finding highlighted that product knowledge is a significant predictor of a consumer's willingness to engage in green purchasing (Kanchanapibul et al, 2014).…”
Section: Ro5: To Examine the Influence Of Product Knowledge On Purcha...contrasting
confidence: 85%
See 1 more Smart Citation
“…Result demonstrates that product knowledge a positive and significant effect on the consumer purchase intention towards green products, which supports H5. The finding is in favour of the results of previous studies of (Han et al, 2017;Groening et al, 2018;Liu et al, 2021;Zollo et al, 2021). The finding highlighted that product knowledge is a significant predictor of a consumer's willingness to engage in green purchasing (Kanchanapibul et al, 2014).…”
Section: Ro5: To Examine the Influence Of Product Knowledge On Purcha...contrasting
confidence: 85%
“…Subsequently, Polonsky et al (2012); Groening et al (2018) identified that green purchasing intentions are deeply influenced by knowledge. Studies identified that product knowledge also significantly affects consumers' green purchases in different context, such as organic food (Nuttavuthisit et al, 2017;Thøgersen et al, 2015), ethical or environmentally fashionable products (Han et al, 2017;Liu et al, 2021) and organic personal care products (Zollo et al, 2021). Accordingly, this study proposes the following hypothesis: H5: Product knowledge positively and significantly influences consumers' purchasing intention towards green products.…”
Section: Product Knowledge and Green Purchase Intentionmentioning
confidence: 84%
“…According to the Theory of Optimal Distinctiveness (Hornsey and Hogg, 1999), individuals tend to join moderately distinct and inclusive groups to fill different or simply fulfill the demand for inclusion (Liu et al, 2021). Besides, consumers always display their identities by associating with prestigious brands to gain status, respect, and exclusivity.…”
Section: Brand Attributes and Intention To The Emotional Consumer-bra...mentioning
confidence: 99%
“…Keyakinan sendiri dimaknai sebagai suatu level kepercayaan (Chen & Chang, 2012). Hal ini menunjukkan bahwa konsumen perlu memiliki pengetahuan mengenai produk yang berkelanjutan untuk mendorong level kepercayaan konsumen terhadap kehandalan produk tersebut sebagai produk yang ramah lingkungan dan etis, sebagai bagian dari makna fashion yang berkelanjutan (Liu et al, 2021). Berdasarkan hasil penelitian Wang et al (2019), pengetahuan akan produk hijau memiliki pengaruh terhadap kepercayaan dan kepercayaan sendiri menjadi mediator hubungan antara pengetahuan dengan purchase intention.…”
Section: Pendahuluanunclassified